Upregulation of DDAH2 Limits Pulmonary Hypertension and Right Ventricular Hypertrophy During Chronic Hypoxia in Ddah1 Knockout Mice - Hannemann, Juliane; Glatzel, Antonia; Hillig, Jonas; Zummack, Julia; Schumacher, Udo; Lüneburg, Nicole; Harbaum, Lars; Böger, Rainer (Frontiers in Physiology, 2020)
Objective. Chronic hypoxia causes pulmonary vasoconstriction leading to pulmonary hypertension and right ventricular hypertrophy. Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of NO synthesis; its level increases in hypoxia concomitantly with reduced activity of dimethylarginine dimethylaminohydrolases (DDAH-1 and DDAH-2), enzymes metabolizing ADMA. Ddah1 knockout mice may therefore help to understand the pathophysiological roles of this enzyme and its substrate, ADMA, in the development of hypoxia-associated pulmonary hypertension. Methods. Ddah1 knock-out mice (KO) and their wild-type littermates (WT) were subjected to normoxia (NX) or hypoxia (HX) for 21 days. We measured ADMA concentration in plasma and lungs, DDAH1 and DDAH2 mRNA and protein expression in the lungs, right ventricular systolic pressure, right ventricular hypertrophy by the Fulton index, and cardiomyocyte hypertrophy by dystrophin staining of the heart. Results. Ddah1 KO mice had higher ADMA concentrations in plasma and in lung tissue than WT in NX (p < 0.05). ADMA significantly increased in WT-HX in plasma and lungs, whilst there were no significant differences in WT-HX vs. KO-HX. This finding was paralleled by a 38±13% reduction in Ddah1 but not Ddah2 mRNA expression, and reduced DDAH1 protein expression but stable DDAH2 protein levels in WT mice. Ddah1 KO mice showed significant elevation of DDAH2 protein but not mRNA levels, which further increased in HX. HX led to increased right ventricular systolic pressure and right ventricular hypertrophy in both, WT and KO mice, with no significant differences between both genotypes. Conclusions. Chronic hypoxia causes an elevation of ADMA, which may impair NO production and lead to endothelial dysfunction and vasoconstriction. Downregulation of DDAH1 expression and activity may be involved in this; however, knockout of the Ddah1 gene does not modify the hypoxia-induced pathophysiological changes of pulmonary blood pressure and right ventricular hypertrophy, possibly due to compensatory upregulation of DDAH2 protein.